2012
DOI: 10.1038/ijo.2012.103
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-day and nutrient composition of eating occasions: prospective association with the metabolic syndrome in the 1946 British birth cohort

Abstract: Background:Diet is a key modifiable factor in the prevention and treatment of the metabolic syndrome. However, few studies have examined the prospective association between time-of-day of nutrient intake and the metabolic syndrome.Objective:To examine the association between time-of-day and nutrient composition of eating occasions and the long-term development of metabolic syndrome in the Medical Research Council (MRC) National Survey of Health and Development (NSHD; 1946 British birth cohort).Methods:The anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 47 publications
12
61
0
Order By: Relevance
“…10 These shifts may contribute to health problems, such as metabolic syndrome. 9 This evidence, combined with the results of our study, suggest that the schedule of regular eating times may be a contributing factor to health disparities as may health disparities contribute to the pattern of dietary intake.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…10 These shifts may contribute to health problems, such as metabolic syndrome. 9 This evidence, combined with the results of our study, suggest that the schedule of regular eating times may be a contributing factor to health disparities as may health disparities contribute to the pattern of dietary intake.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, the methods used to create the temporal dietary patterns described in this paper have addressed some of the obstacles noted in previous studies. 11 The use of time of day, frequency, and proportional energy intake for clustering rather than reported eating occasion labels, 52,53 or consolidated time blocks by eating occasions, 9,10 limits the bias that researchers and study participants may place on the names assigned to eating occasions throughout the day. A limitation was the examination of all days in the analysis rather than separate examination of weekdays and weekend days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, timeof-day of macronutrient intake is critical to obesity, given that lipid and glucose metabolism are influenced by the circadian rhythm, a topic reviewed in a recent article by Oosterman et al (61) . Consistent with this, a longitudinal association between carbohydrate intake at breakfast and the abdominal obesity component of the metabolic syndrome was observed in the 1946 British Birth Cohort (46) . Likewise Dubois et al reported that overweight/obesity in breakfast skippers was related to a higher carbohydrate intake at dinner (41) .…”
Section: Summary Of the Evidence And Current Challengessupporting
confidence: 66%
“…An improvement of glycaemic control was also observed when carbohydrates were mainly eaten at dinner and protein mainly at lunch18. In contrast, epidemiological studies propose a beneficial effect of a carbohydrate-rich diet at the beginning of the day: an increasing carbohydrate intake at the expense of fat in the morning was shown to be protective against the development of diabetes19 and metabolic syndrome20.…”
mentioning
confidence: 99%